Marathons in altitude - Roi, G. S.; Giacometti, M.; von Duvillard, S. P. (Medicine & Science in Sports & Exercise, 1999)
Marathon performance in altitude is mainly affected by the lower VO2max. The better performance of elite marathoners in altitude compared with good runners was related to the higher % of VO2max maintained during every marathon. The differences between the expected and the observed performances at high altitude depend on the uneven running path and on a poorer economy of running that is related to the higher mechanical work of breathing. The fractional utilization of VO2max seems lowered by acute exposure to altitude and slightly increases with acclimatization.